An experimental study on the immunization of mice and rabbits with Pasteurella multocida toxoid - Sunder, Jai; Kumar, A A (The Indian Journal of Animal Sciences, 2012)
A toxigenic strain of Pasteurella multocida serotype A: 12 of goat origin was selected on the basis of its toxin yield amongst other 3 toxin producing strains with a view to study its immune response. A crude Pasteurella multocida toxin (PMT) was prepared by cell sonication method. The immune response of inactivated PMT (toxoid) was studied in mice and rabbit model. The immune status of vaccinated animals was determined by ELISA and challenge test with crude toxin and live culture. Mice vaccinated with 2 doses schedule comprising 10 mg and 100 mg by s/c route gave a protection level of 60.0% and 73.3%, respectively, on challenge with 200 mg of crude toxin. Almost same level of protection was observed when challenged with live culture, 0.2 ml s/c (10Â¯â¹). While rabbits immunized with 200 mg of toxoid by s/c routes were protected when challenged with 400 mg of crude toxin by intranasal route and also did not show any dermonecrotic effect of PMT when 300 mg of crude toxin was given by I/D route.